Correction: Conformational changes in amyloid-beta (12–28) alloforms studied using action-FRET, IMS and molecular dynamics simulations. Issue 2 (18th November 2015) - Daly, Steven; Kulesza, Alexander; Poussigue, Frederic; Simon, Anne-Laure; Choi, Chang Min; Knight, Geoffrey; Chirot, Fabien; MacAleese, Luke; Antoine, Rodolphe; Dugourd, Philippe
Abstract : Correction for 'Conformational changes in amyloid-beta (12–28) alloforms studied using action-FRET, IMS and molecular dynamics simulations' by Steven Daly et al., Chem. Sci., 2015, 6, 5040–5047.